Investigation of The Clinical and Microbiological Effects of Different Toothpastes: In-Vivo Study - Mine Koruyucu; Sinem Birant; Nursen Topçuoğlu; Figen Seymen; Güven Kulekci (Cumhuriyet University, 2020)
Objectives: The purpose of this study is to compare the clinical, antibacterial and microbiological effects of the non-fluoride and fluoride toothpastes. Materials and Methods: In this study eighty children (3 to 12 years old) were divided into four groups and followed for four weeks. First and second groups (40 children, 6-12 years) used different fluoride toothpastes; third and fourth groups (40 children, 3-5 years) used nonfluoride toothpastes. The halitosis score, plaque index, gingival index, bleeding index, buffering capacities, Mutans Streptococci, Lactobacilli and yeast counts were recorded on 1st day, 7th day, 15th day and 30th day. First and second group; third and fourth group were compared with each other. Data were analyzed statistically by using Mann Whitney U tests, Wilcoxon Sign Test, Fisher Freeman Halton Exact Test and Mc Nemar Test with a significance level of p<0.05. Results: Statistically significant association was not found in the mean scores of halitosis, gingival index, plaque index, bleeding index, buffering capacity, Mutans Streptococci, Lactobacilli and yeast (p>0.05), between groups on first day. All four toothpastes produced statistically significant reductions from 1st day to 30th days in scores of halitosis, plaque index, gingival index, bleeding index and buffering capacity (p<0.01; p<0.05), within groups. Statistically significant reductions was found according to in Mutans Streptococci, counts from 1st day to 30th day for group 1, 2 and 3 (p<0.05); but was not found statistically significant changes in group 4 on the 30th days(p>0.05). Conclusion: All tested toothpastes proved to be safe and significantly effective clinical and microbiological features.